Natural and socio-cultural factors of epidemics (plague, smallpox): The example of the Adyghe population of the Northwest Caucasus - S. H. Khotko; N. A. Pocheshkhov; R. M. Shkhachemukov (Кубанский научный медицинский вестник, 2024)
Background. The article discusses the problem of the impact of epidemic diseases on ethnogenesis. As an ancient agricultural ethnic group in contact with nomadic and Mediterranean populations, the Adyghe were formed during periods of frequent epidemics of dangerous diseases caused by the process of animal domestication and subsequent impact of anthropogenic factors. The devastating effect of smallpox and measles pandemics was felt following the establishment of intensive trade exchange during the 2nd century CE by the Roman and the Han empires. The first plague pandemic (beginning with the “Justinianic Plague”, 542–543) mostly affected the Balkans and the Eastern Mediterranean. The second plague pandemic, the so-called “Black Death” (1346–1353), which appeared in the center of the Mongol Empire, quickly spread via caravan routes across most of Eurasia. The scale of the epidemic was influenced by the pathogenic complex that had developed by the 14th century, which included humans, the bacterial pathogenic agent itself, and its carriers (large rodents especially black rats, fleas). Factors such as famine caused by overpopulation, low standards of personal and public hygiene, the prevalence of wooden buildings in cities and towns, the fur trade, etc., also had contributory effects. Objectives. The study set out to identify the natural and the socio-cultural factors that influenced the spread of the plague and the smallpox epidemics in the North-West Caucasus. Methods. The data on which this study is based are formed from collections of narrative sources (Russian, Arabic-Persian, European), archaeological and historical-anthropological works, medical and genetic studies (electronic platforms: eLIBRARY.RU, Academia.edu, CyberLeninka, J-STAGE [Japan Science Technology Information Aggregator, Electronic]). Research methods: historical and comparative, on which basis a comparative analysis of the impact of the plague pandemic of the mid-14th century centering on contact between on nomadic and sedentary ethnic groups (Mongols and Russians, Mongols and Circassians) was carried out; the individualizing comparison method, which was used to identify the specific means by which the Circassian ethnic group overcame the Black Death pandemic; the systems analysis method, on which basis the roles of pathogenic complex and anthropogenic factors in the course of epidemics were compared. Results. The results of the analysis show that the population of the North-West Caucasus were affected by the Black Death plague of the mid-14th century to a significantly lesser extent than the urban centers of the Golden Horde, Rus’ and Europe. The serendipitous failure of the pathogenic complex in the former region was due to the following natural and anthropogenic factors: (1) the North-West Caucasus (more precisely, the entire area to the west of the Teberda River) was naturally bereft of effective carriers of the plague bacillus (marmots, gophers, etc.); (2) Matrega and Copa, the two contemporaneous Circassian towns serving as ports for the shipment of grain and other agricultural products, were located on the periphery of the Adyghe settlement area; (3) the dispersed, farmstead way of life among the estuaries and the complex network of peninsulas of the Kuban Delta, mountains and forests of the NWC contributed to the rapid adoption of quarantine measures; (4) a reliable vitamin-rich nutrition system (sturgeon and their caviar, goat meat and cheese, fruit, honey, etc.); (5) a well-developed system of hygiene and disease prevention (smallpox, malaria), whose existence was retrospectively established based on sources from the 17th–19th centuries. Conclusion. The plague pandemic that took place within the unified space of Mongol imperial communications had a huge impact on the historical fate of the Adyghe ethnic group, which was manifested in their paradoxical numerical growth against the backdrop of general depopulation. Against the backdrop of frequent epidemics, Adyghe developed strict and quite effective rules for preserving life and health, covering disease prevention, personal and public hygiene. Some particularly impressive practices, if not created by Adyghe folk medicine, then preserved there and later transmitted to Ottoman Turkey and Western Europe, was manifested in the original practice of smallpox inoculation.